2022
DOI: 10.4028/p-4ewmy1
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Analysis of Xylanase and Cellulase Production from Pineapple Peel Waste

Abstract: Pineapple wastes (skin, core and crown) are mainly composed of carbohydrates (cellulose, hemicellulose, and lignin). Non-starch polysaccharides (NSP) in feed are indigestible by the endogenous enzymes in poultry. Thus, exogenous enzymes (xylanase and cellulase) are required to overcome this problem. Due to high fiber content, pineapple wastes are unsuitable for animal feed. However, the fermented waste juice could be used to produce enzymes. The objective of this study is to produce xylanase and cellulase from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Design-Expert® software (Version 7.1.6, Stat-Ease, Inc., Minneapolis, MN) was used to analyse and construct the screening experimental design of the fermentation process parameters in the enzyme synthesis from the pineapple waste juice fermentation [14]. Incubation period, temperature, pH of the medium and substrate concentration were chosen as four parameter components in a 2 4 partial factorial design.…”
Section: Experimental Design and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Design-Expert® software (Version 7.1.6, Stat-Ease, Inc., Minneapolis, MN) was used to analyse and construct the screening experimental design of the fermentation process parameters in the enzyme synthesis from the pineapple waste juice fermentation [14]. Incubation period, temperature, pH of the medium and substrate concentration were chosen as four parameter components in a 2 4 partial factorial design.…”
Section: Experimental Design and Analysismentioning
confidence: 99%
“…Waste from pineapple also can be a source of proteolytic enzyme, which is widely used as a therapeutic and meat-tenderiser [12]. Several enzyme fermentation researches have been done by using pineapple waste [11]; [13]; [14]. However, most of the research focused on enzymes such as cellulase, xylanase and pectinase.…”
Section: Introductionmentioning
confidence: 99%
“…The Malaysia Pineapple (Ananas comosus) is a typical tropic fruit with a total production of between 16 and 19 million tonnes around the world annually [8]. Generally, pineapple is consumed as fresh fruits or is processed into salads, fruit cocktail, jam, and can.…”
Section: Introductionmentioning
confidence: 99%
“…Pineapple wastes are a rich source of GE, which contains abundant proteases, amylases, and lipases. The pineapple and citrus peelsderived GE have high levels of protease, lipase, and amylase activity, which aid in the breakdown of TKN (Total Kjeldahl Nitrogen), COD (Chemical oxygen demand), and TP (Total phosphorus) in waste activated sludge and landfill leachate, increasing their solubilization [8,9]. Jiang et al, [11] reported that adding GE effectively reduced the NH3 emission and increased the TN (Total Nitrogen) content of the end compost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation